KESESUAIAN MASYARAKAT JAWA DALAM NOVEL MANTRA PEJINAK ULAR DENGAN REALITA: ANALISIS SOSIOLOGI SASTRA - Kustri Sumiyardana (Balai Bahasa Provinsi Riau, 2017)
Mantra Pejinak Ular (Spell of Snake Peek) is a novel by Kuntowijoyo. The setting of the novel is located in Central Java, especially Klaten and Karanganyar. Because the literature is a mirror of society in its time, the novel tells the state of the Javanese society. Through the approach of sociology of literature, it can be seen that the community displayed in Mantra Pejinak Ular is in accordance with the reality of society in Java. The suitability, among other livelihoods, beliefs, and typical attitudes of Javanesse society. It proves that the novel Mantra Pejinak Ular waswritten by observation and appreciation of the author to the Javanesse community.